Differentiation of two taxa of caulerpa based on tufa marker / Maryam Dalili Shofaei - Shofaei, Maryam Dalili (2011)
The Caulerpa is an economical important genus among chlorophyta, which was initially described by Lamouroux in 1809, since then some 70 species of Caulerpa have been identified. The Caulerpa species have complex morphology that provides some characters that can be used in taxonomy, but extensive plasticity makes species boundaries difficult to be defined. With advancement in the field of molecular biology, it provides some alternatives for better understanding of taxonomy. In this study, PCRbased molecular techniques were used in an attempt to differentiate two taxa of Caulerpa based on tufA marker. In this research work, specimens were collected from Pulau Redang, Terengganu, Malaysia. Based on the morphology of the assimilators, specimens were identified into two species namely Caulerpa serrulata var. serrulata and Caulerpa serrulata var. boryana. Caulerpa DNA was extracted using DNeasy Plant Mini Kit followed by Polymerase Chain Reaction (PCR), with amplification parameters optimized to obtain reproducible results for gene sequencing. Based on phylogenetic analyses, it is inferred that Caulerpa serrulata var. serrulata and Caulerpa serrulata var. boryana are the same species although different morphological characteristics were observed. Both the Maximum Parsimony (MP) and Bayesian Inference (BI) analyses have shown the two varieties are monophyletic and supported with high bootstrap values. From this study, tufA marker is suitable in resolving the genetic relationship between Caulerpa serrulata var. serrulata and Caulerpa serrulata var. boryana.